Imaji Identitas Nasional di Ruang Diaspora Anggota PPI di Thailand - M. Rifaldi Akbar (Antropologi Indonesia, 2019)
National identity is a construct that grows in the memories of the nation’s members. In a diaspora space, Indonesian national identity has a more significant role than local identities. This article explores the articulations of national identity by the members of the Indonesian students abroad (PPI) in Thailand. As foreign students, they encounter with people from other nations who have limited knowledge about polyethnic Indonesia in daily basis. Thus, they are trapped in a space that requires them to define Indonesia. Therefore, the representation of national identity becomes the autonomy of each PPI member. This article argues that the similarity of language, jokes, food standards, and habits bring PPI members together and strengthen their national identity. Using ethnography in a micro space, this article tries to describe how the similarities facilitate the formation of an imagination of national identity in a diaspora space.